Occupational lung diseases: from old and novel exposures to effective preventive strategies. Issue 5 (May 2017) - Cullinan, Paul; Muñoz, Xavier; Suojalehto, Hille; Agius, Raymond; Jindal, Surinder; Sigsgaard, Torben; Blomberg, Anders; Charpin, Denis; Annesi-Maesano, Isabella; Gulati, Mridu; Kim, Yangho; Frank, Arthur L; et al.
Summary: Occupational exposure is an important, global cause of respiratory disease. Unlike many other non-communicable lung diseases, the proximal causes of many occupational lung diseases are well understood and they should be amenable to control with use of established and effective approaches. Therefore, the risks arising from exposure to silica and asbestos are well known, as are the means of their prevention. Although the incidence of occupational lung disease has decreased in many countries, in parts of the world undergoing rapid economic transition and population growth—often with large informal and unregulated workforces—occupational exposures continue to impose a heavy burden of disease. The incidence of interstitial and malignant lung diseases remains unacceptably high because control measures are not implemented or exposures arise in novel ways. With the advent of innovative technologies, new threats are continually introduced to the workplace (eg, indium compounds and vicinal diketones). In developed countries, work-related asthma is the commonest occupational lung disease of short latency. Although generic control measures to reduce the risk of developing or exacerbating asthma are well recognised, there is still uncertainty, for example, with regards to the management of workers who develop asthma but remain in the same job. In this Review, we provide recommendations for research, surveillance, and other action for reducing the burden of occupational lung diseases.